«Visse tutta una lunga vita a fare professione di pessimismo»: Michelstaedter vs Schopenhauer «He lived a long life doing profession of pessimism»: Michelstaedter vs Schopenhauer - Roberta Visone (Fuori Collana, 2018)
This paper examines the meaning of Carlo Michelstaedter's judgement on Arthur Schopenhauer, according to which Schopenhauer does not fully accept the consequences of his own system of thought but only makes a «profession of pessimism», in the light of Michelstaedter's categories of «Persuasion» and «Rhetoric».